New Insights Into Chromomere Organization Provided by Lampbrush Chromosome Microdissection and High-Throughput Sequencing - Zlotina, Anna; Maslova, Antonina; Pavlova, Olga; Kosyakova, Nadezda; Al-Rikabi, Ahmed; Liehr, Thomas; Krasikova, Alla (Frontiers in Genetics, 2020)
Giant lampbrush chromosomes (LBCs) typical for growing oocytes of various animal species are characterized by a specific chromomere-loop appearance and massive transcription. Chromomeres represent universal units of chromatin packaging at LBC stage. While quite good progress has been made in investigation of LBCs structure and function, chromomere organization still remains poorly understood. To extend our knowledge on chromomere organization, we applied microdissection to chicken LBCs. In particular, 31 and 5 individual chromomeres were dissected one by one along the macrochromosome 4 and one microchromosome, respectively. The data on genomic context of individual chromomeres was obtained by high-throughput sequencing of the corresponding chromomere DNA. Alignment of adjacent chromomeres to chicken genome assembly provided information on chromomeres size and genomic boarders, indicating that prominent marker chromomeres are about 4-5 Mb in size, while common chromomeres of 1.5 to 3.5 Mb. Analysis of genomic features showed that the majority of chromomere-loop complexes combine gene-dense and gene-poor regions, while massive loopless DAPI-positive chromomeres lack genes and are remarkably enriched with different repetitive elements. Finally, dissected LBC chromomeres were compared with chromatin domains (topologically associated domains (TADs) and A/B-compartments), earlier identified by Hi-C technique in interphase nucleus of chicken embryonic fibroblasts. Generally, the results obtained suggest that chromomeres of LBCs do not correspond unambiguously to any type of well-established spatial domains of interphase nucleus in chicken somatic cells.